MASALAH PENAHANAN IJAZAH DALAM PERSPEKTIF ETIKA DUNIA KERJA - Matang; Istiqomah Nurul Azizah (CV. Cendikiawan Muda Sriwijaya, 2026)
The practice of withholding diplomas by companies amidst the dynamics of the labor market still occurs in Indonesia. Diplomas as proof of career qualifications are kept and withheld under the guise of guaranteeing worker loyalty. This practice is inconsistent with human rights for workers because of freedom, self-development, and a decent living as as guaranteed by articles 27 and 34 of the 1945 Constitution. This study aims to examine the issue of withholding diplomas from the perspective of work ethics and basic workers' rights. Using a qualitative method of literature review approach, data were obtained from scientific journals, books, and other relevant publications regarding withholding diplomas. Descriptive data analysis techniques identify common patterns, ethical arguments, and social implications of the practice of withholding diplomas. The research findings show that withholding diplomas occurs because of agreements at the beginning of the contract that ethically violate human rights and pose a risk of loss to workers. The lack of clear regulation in Law No. 13 of 2003 on Manpower exacerbates the issue, creating loopholes that allow companies to place workers in vulnerable positions.